The public uses of coercion and force from constitutionalism to war (New York Oxford University Press, 2021)
The need to replace force with law is central to a Kantian theory of war. In such a theory the only ground for using force is the prevention of wrongful force. War is barbaric and wrongful. A key theme in Kantian political and legal philosophy is every individual's right to independence, which can only be secured through a legitimate state, which in turn is obliged to repudiate war and pursue peace. Yet the Kantian project of achieving perpetual peace among states seems (at best) an unfulfilled hope. The wider category of global justice does not fare much better, at least according to most theorists. The modern state is often portrayed as a major obstacle to both peace and global justice. Kantian theories are distinctive insofar as they try to carve out a relatively hopeful role for the state in international affairs, though one that is grounded in an analysis of the state's nature rather than being driven by completely abstract moral considerations. Modern states' authority claims and their exercise of power and sovereignty span a spectrum from the most stringently and explicitly codified- the constitutional level- to the most fluid and turbulent- acts of war. Inter alia, that suggests a specific connection between constitutionalism and just war theory, as both concern the justifiability of state action vis- à- vis individuals as well as states. This book aims to explore that connection through the lens of the relationship between law and (just) war theory from a Kantian perspective. The various contributions in this book investigate both extremes of the spectrum: national and transnational constitutionalism and acts of war, and their relationship. The key questions considered- directly or indirectly- by all the contributors are the following: what, if any, are the normatively salient differences between states' internal coercion and the external use of force? Is it possible to isolate the constitutional level from other aspects of the state's coercive reach? How could that be done while at the same time guaranteeing a robust conception of human rights and adherence to the rule of law? Likewise, is war an extension of political practice or an alternative to it? New forms and technologies of warfare raise further fundamental questions about due process, individual responsibility, fairness, and broader questions pertaining to justice and the responsibility to protect. From a constitutional perspective, questions concern the justification for state action, the human rights framework, and the question of judicial review and proportionality reasoning in "emergency" contexts. The purpose of the book is to combine political theory on war, philosophy of law, criminal law theory, and constitutionalism scholarship in order to provide a new platform for understanding the contemporary law of war through a Kantian prism"--
semi-Kantian just war theory / Yitzhak Benbaji -- Might and right : Ripstein, Kant and the paradox of peace / Rainer Forst -- Reading Kant's Rechtslehre: some observations on Ripstein's Kant and the law of war / Thomas Mertens -- The moral basis of state independence / Anna Stilz -- Vulnerability, space, communication : three conditions of adequacy for cosmopolitan right / Peter Niesen -- Three models of territory : Arthur Ripstein on the territorial rights of states / Alice Pinheiro Walla -- A Kantian defense of remedial wars / Alon Harel -- National defense and the value of independence / Massimo Renzo -- Exactitude and indemonstrability in Kant's doctrine of right / Katrin Flikschuh -- The right to wage private wars of subsistence : its nature, grounds, and place in revisionist just war theories / Johan Oltsthoorn -- Between wormholes and blackholes : a Kantian (Ripsteinian) account of human rights in war / Aravind Ganesh -- Kant and the criminal law of war / Malcolm Thorburn -- EU solidarity as collective self-defense? : constitutionalism and the public uses of force / Ester Herlin-Karnell -- Europe's cosmopolitan union : a Kantian reading of EU internal market law and the refugee crisis / Bertjan Wolthuis and Luigi Corrias -- From constitutionalism to war-and back again : a reply / Arthur Ripstein.
Includes bibliographical references and index.
Keywords: Kant, Immanuel -- 1724-1804.; Just war doctrine. -- Electronic book; Constitutional law -- Philosophy; War (International law) -- Philosophy